Analysis Of The Utilization of Covid 19 Poster Media in Learning Narrative Writing in Class IV Students of SDN Keseneng - Khoirunnisaq Khoirunnisaq (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research is a quantitative research. This research method uses phenomenological research methodology, to explore the phenomena that occur and their novelty. This study aims to describe the feasibility of the Covid 19 alert poster as a medium in learning to write narrative for fourth grade students of SD Negeri Keseneng. In addition, this study also aims to determine student responses to the use of the Covid 19 alert poster media in learning to write narrative for fourth grade students of SD Negeri Keseneng. The subjects of this study were 20 students of grade IV SD Negeri Keseneng. Data collection techniques used in this study were observation, interviews, and documentation. Data collection tools in this study were observation guidelines, interview guides, and documentation. Based on the discussion conducted, the researchers concluded that the Covid 19 alert poster media was worthy of being used as a medium in learning to write narratives because it was easy to find, practical, and interesting. In addition, it is also known that students' responses to using poster media are good.